PENGARUH PEMBERIAN PUPUK ORGANIK CAIR URIN SAPI DAN UREA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI - Syaiful Akbar Arani (UNIVERSITAS LABUHANBATU, 2019)
The aim of this study is to know the influence of the giving of Liquid Organic fertilizer (POC) Cow Urine and Urea Fertilizer production plant growth and against mustard (Brassica juncea L.). This research was carried out in Village Aek Batu Subdistrict Torgamba Regency Labuhanbatu of North Sumatra in + 70 mdpl. Designs used are Random Design Group (RAK) Factorial with two factors, namely the granting of liquid organic fertilizer factor (POC) cow urine with 4 degrees of treatment (N0:0 cc/plant, N1:5 cc/plants, N2:10 cc/tanamana and N3:15 cc/plant) and urea fertilizers with awarding 3 adequate treatment (U1:1 gr/plant, U2:2 gr/plant and U3 : 3 gr/plant). The parameters observed were higher plants (cm), number of leaf worthy of consumption (strands), biomass sample (gr) fresh weight and sell sample (gr). Of research results obtained the following conclusions: 1. liquid organic fertilizer Treatment of cow urine shows the very real influence against the high number of fresh leaves of the plant and worthy of consumption at the age of 24 HST while Weight biomass fresh weight of sample and sell sample shows real influence. 2. urea fertilizer Treatments showed no real influence of age 10-17 HST but real effect at age 24 HST on higher plants. Whereas the amount of the fresh leaf is worthy of consumption, biomass weight and weight fresh sample and sell weight sample shows the influence of unreal age 24 HST. 3. The interaction between organic fertilizer liquid fertilizer and cow urine urea showed no real influence on all the parameters are observed i.e. High number of plants, the fresh leaf is worthy of consumption, biomass weight and weight fresh sample and sell weight sample. Keywords : Liquid Organic Fertilizer (POC) Cow Urine, Urea Fertilizer, Plant growth and the production of Mustard (Brassica juncea L.).